Penicillin Production By Penicillium Chrysogenum L112 With Variation Of Agitation Speed In 1 L Fermentor - Anwar, Hairul (Yayasan Rahmatan Fiddunya Wal Akhirah, 2024)
Penicillin refers to a group of β-lactam antibiotics with high commercial value because it is precursor for semi synthetic antibiotics such as amoxicillin and ampicillin. It also has high antibacterial activity. Penicillin production in industrial scale uses large fermentation reactor which require optimum agitation. The present study was conducted to investigate the effect of agitation speed on penicillin production using Penicillium chrysogenum L112, which have high antibiotics activity against some bacteria. P. chrysogenum L112 which regenerated at 30°C for 7 days was suspended with distilled water. The suspension was inoculated to vegetation media to reach 2% (v/v) final concentration. It was then followed by activation at 28°C for 60 hours with 120 rpm agitation speed. The activated culture was inoculated to fermentation media to give 10% (v/v) final concentration in a 1 L fermenter at pH 7 and 28°C, aeration of 1 vvm, for 240 hours. Agitation speed was varied at 100, 150 and 200 rpm. Sample was collected every 24 hours and checked for its pH, dry cell weight, and antibiotics activity. The results of the present study indicate that agitation speed and time of incubation affected the P. chrysogenum ability to produce penicillin. The crude extract showed different effect when tested against different bacteria, which indicate different amount of penicillin produced. The best antibiotics activity was found at 150 rpm agitation speed, incubation time of 192 hours. The highest inhibition was found for Escherichia coli which showed 37 mm clear zone.